Informing a position statement on the use of artificial intelligence in dermatology in Australia. (15th November 2022) - Caffery, Liam J.; Janda, Monika; Miller, Robert; Abbott, Lisa M.; Arnold, Chris; Caccetta, Tony; Guitera, Pascale; Shumack, Stephen; Fernández‐Peñas, Pablo; Mar, Victoria; Soyer, H. Peter
Abstract: Artificial Intelligence (AI) is the ability for computers to simulate human intelligence. In dermatology, there is substantial interest in using AI to identify skin lesions from images. Due to increasing research and interest in the use of AI, the Australasian College of Dermatologists has developed a position statement to inform its members of appropriate use of AI. This article presents the ACD Position Statement on the use of AI in dermatology, and provides explanatory information that was used to inform the development of this statement.